Neil Young [videorecording (DVD)] : journeys - Demme, Jonathan, 1944-2017; Demme, Jonathan, 1944-2017; Young, Neil, 1945- (Sony Pictures Home Entertainment, 2012)
Documentary on folk rock musician Neil Young, covering two nights on his solo tour at Massey Hall in Toronto. The concert includes new music from Young's album Le Noise, as well as the classics Ohio; I Believe in You; and others. Mixed in with concert footage are scenes from a road trip through Ontario, Canada.